104k views
0 votes
F(x) = x^2- 4x , g(x) = 2 – 3x
it wants to know the (f-g) (-5)

2 Answers

2 votes

You have to remember that
(f-g)(-5) = f(-5) - g(-5) , then first evaluate each one separately, and finish by subtracting them.


\begin{aligned}(f-g)(-5)& = f(-5) - g(-5)\\[0.5em]&= [ (-5)^2 - 4(-5)] - [2-3(-5)]\\[0.5em]&= [ 25 +20] - [2+15]\\[0.5em]&= 45- 17\\[0.5em]&= 28\end{aligned}

User Andrew Garrison
by
5.4k points
2 votes

Answer:

(f - g)(-5) = 18

Explanation:

~Subtract both functions

(x^2 - 4x) - (2 - 3x)

~Simplify

(x^2 - 4x) + (-2 + 3x)

~Simplify by combining like terms

x^2 + x - 2

~Substitite -5 and solve

(-5)^2 + (-5) - 2

25 - 5 - 2

20 - 2

18

Best of Luck!

User Larry Lustig
by
5.6k points